eSports under discussion: A new sports discipline? - Perrino Peña, Maria; Martínez-Rodríguez, José Antonio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Video games have been growing in terms of social implantation as technology advance and generations have become more digital. Competitive modalities are named ‘eSports’. The pandemic caused by COVID-19 further accelerated the growth of these practices. Therefore, there are those who propose that these events should be configured as a new sports discipline, however there are other voices against it. This study aimed to explore the current situation and reconsider the concept of eSports from a legal perspective in Spain and other countries. The study primarily employed a qualitative methodology with a phenomenological approach, focusing on a review of scientific literature and an analysis of legislative documents. The study showed that the term "eSports" is largely a strategic label and not an actual representation of a sport, and the authors propose "eGames" or competitive electronic games as a more appropriate nomenclature. Governing frameworks treating these activities as sports are essentially non-existent and, where they exist, are on the basis of political, social, or economic considerations. Furthermore, eGames should be considered part of the leisure and entertainment sector, with specific legal provisions ensuring safe and sustainable development.